Quality of life related to health, anxiety and depression in people with cardioverter defibrillators - Pulido-Montes, Maria Andreina; Bueno-Robles, Luz Stella (Universidad y Salud, 2021)
Introduction: Cardiovascular diseases have caused a rise in arrhythmias, increasing the use caridoverter defibrillators. Although, these devices prevent arrhythmias, they may also affect the quality of life. Objective: To describe the association between quality of life and health, anxiety and depression in people who use cardioverter defibrillators. Materials and methods: A qualitative, descriptive, correlational and cross-sectional study was carried out with 85 patients using implantable cardioverter defibrillator. Sociodemographic records, the Health Questionnaire (SF-36), and the Beck Anxiety and Depression Questionnaire were used. Results: 81.2% of participants were men with their ages ranging between 36 and 92 years. The health-related quality of life showed a negative correlation with respect to anxiety (r = - 0.622) and a slight correlation with depression (rs = -0.599; p<0.001). Conclusions: The use of a cardioverter-defibrillator can trigger anxiety and depression that can deteriorate the health-related quality of life if not timely intervened. It is important to implement early actions that generate well-being.